Students’ Problem‑Solving Skills and Gender‑Based Comparison in Thermodynamics through the STEM Approach - Jewaru, Aurelia Astria L.; Hasanah, Syifa’ul; Parno; Tefa, Maria; Maubuthy, Markus Simeon K. (Program Studi Pendidikan IPA FKIP Universitas Jember, 2025)
Problem-solving skills through the STEM approach are currently also being examined in relation to gender differences. This study aims to describe students’ problem-solving skills and compare them based on gender in the topic of thermodynamics using the STEM approach. The research employed a descriptive quantitative method involving 86 grade 11 science students, consisting of 51 female and 35 male students. The problem-solving indicators used include Useful Description, Physics Approach, Specific Application of Physics, Mathematical Procedure, and Logical Progression. Data were analyzed using descriptive statistics and comparative tests. The results showed that, in general, students’ problem-solving abilities were in the “good” category. The comparative analysis revealed that female students outperformed male students in the Useful Description and Logical Progression indicators, while male students showed higher performance in Specific Application of Physics and Mathematical Procedure. No significant difference was found between the two groups in the Physics Approach indicator. Overall, the total score of students’ problem-solving skills indicated no significant difference between female and male students. These findings suggest that the STEM approach fosters equitable opportunities for both genders to develop physics problem-solving skills, despite differences in specific indicator strengths. Therefore, STEM-based learning should be designed contextually and inclusively to accommodate students’ diverse potentials and cognitive styles in a balanced manner.